Evolução do Strongyloides venezuelensis em camundongos submetidos ao etilismo agudo - Maia, Caroline Ohnesorge (2015)
The prevalence of Strongyloides stercoralis in chronic alcoholics is greater than in non-alcoholics. As the mechanisms involved in this higher prevalence remain unclear, we plan to evaluate the effect of ethanol intoxication in the course of infection by S. venezuelensis in mice, the model considered similar to S. stercoralis. Two models of intoxication with ethanol were used: (a) an episode of acute alcoholism (7 mg/g body weight ethanol 40% by gavage (EA group), (b) three episodes of acute alcoholism (5 mg/g body weight 40%) at an interval of one week in mice treated with 15% ethanol (at water ad libitum), at three weeks and during the period after infection (EA/C group.) Male Swiss mice were infected with 700 L3 larvae of Strongyloides venezuelensis, one hour after gavage with ethanol. The course of the infection was accompanied by: (a) egg counts in the feces daily until complete disappearance (b) larvae counts in the lung 48 hours after infection, and (c) counting adult worms in the gut 8 (EA group) or 9 days (Group AE/C) after infection. It was held total leukocyte and eosinophil 4 days interval from the second day after infection. The results showed (1) in both groups that received ethanol, egg counts and the number of worms recovered from the intestine were higher than the respective control groups; (2) at EA group, the number of larvae recovered in the lung was higher than the control group, which was not observed in the EA/C group; (3) there was no significant difference in the behavior of total leukocytes and eosinophils, although there were fewer tendency on the second day after infection in the groups treated with ethanol. In conclusion, one episode, or three episodes with an interval of one week in acute alcohol administered in animals receiving 15% of ethanol, changed the kinetics of S. venezuelensis infection in mice, with an increase in the elimination of eggs and the recovery of adult worms of intestine, with no differences related to the model of an ethanol intoxication.